2017
DOI: 10.1159/000477211
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Interferon Regulatory Factor 1 Regulates Lipopolysaccharide-Induced VCAM-1 Expression Independent of NFκB

Abstract: Sepsis is a severe systemic inflammatory response to infection. Endothelial activation and dysfunction play a critical role in the pathophysiology of sepsis and represent an important therapeutic target to reduce sepsis mortality. Interferon regulatory factor 1 (IRF-1) was recently identified as a downstream target of TNF-α-mediated signal transduction in endothelial cells. The aim of this study was to explore the importance of IRF-1 as a regulator of lipopolysaccharide (LPS)-induced endothelial proinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
1
28
2
Order By: Relevance
“…It has been reported that TNF‐α can induce Klotho reduction in animal models of kidney injury or systemic inflammation . Moreover, IRF‐1 is identified as a downstream target of TNF‐α‐mediated signal transduction in sepsis . However, In present study, our results indicated that the enhanced expression of IRF‐1 after UUO may be induced by TNF‐α, followed by Klotho reduction in tubular epithelial cells and renal fibrosis.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…It has been reported that TNF‐α can induce Klotho reduction in animal models of kidney injury or systemic inflammation . Moreover, IRF‐1 is identified as a downstream target of TNF‐α‐mediated signal transduction in sepsis . However, In present study, our results indicated that the enhanced expression of IRF‐1 after UUO may be induced by TNF‐α, followed by Klotho reduction in tubular epithelial cells and renal fibrosis.…”
Section: Discussioncontrasting
confidence: 70%
“…58,59 Moreover, IRF-1 is identified as a downstream target of TNF-α-mediated signal transduction in sepsis. 40 However, In present study, our results indicated that the enhanced expression of IRF-1 after UUO may be induced by TNF-α, followed by Klotho reduction in tubular epithelial cells and renal fibrosis. To some extent, the results also suggested that the inhibition of TNF-α on the expression of Klotho may be achieved by upregulating IRF-1.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…The key importance of and continued research interest in Toll-like receptors are reflected in the articles by Yan et al [16] and Koymans et al [17]. Despite the fact that the discovery of their importance in innate immunity was more than 2 decades ago, they continue to surprise with regard to their broad effects on regulating both innate and adaptive immunity [18,19,20,21].…”
mentioning
confidence: 99%